Some Features Of Education In Higher Educational Institutions Of Law Enforcement Agencies - Vyacheslav Mikhailovich Ilyin (Genius Journals, 2025)
This article analyzes the relevance of pedagogical technologies in the development of higher education and their specific use in the training of personnel in higher educational institutions of law enforcement agencies.
Keywords: pedagogical technologies; pedagogical process; interactive learning